Cephalopods, small vertebrate fauna and stable isotope (δ13C, δ18O) record from the Jurassic-Cretaceous transition (uppermost Crassicollaria through Calpionella Zones) of the Outer Western Carpathians, Kurovice quarry (Czechia). (December 2018) - Košťák, Martin; Vaňková, Lucie; Mazuch, Martin; Bubík, Miroslav; Reháková, Daniela
Abstract: An unusual and very important macrofauna has been recorded in the deep water environment (i.e. below the aragonite CCD) of the uppermost Tithonian – lower Berriasian carbonate calpionellid-bearing sequence of the Kurovice section (Czechia). Rhyncholites, belemnites, and small vertebrate fauna of elasmobranchians (Neoselachii) are reported herein from a submarine slump probably resulting from a tsunami-like event. The Jurassic – Cretaceous (J/K) boundary interval is well demarcated by the occurrence of small globular Calpionella alpina, the J/K boundary marker established by the Berriasian Working Group. Rhyncholites, belemnites, and elasmobranchians are re-evaluated herein within the modern taxonomic concept, and they are stratigraphically investigated. High resolution sampling provided new data on the stable isotope record (δ 13 C and δ 18 O) from the uppermost part of the Crassicollaria through the Calpionella Zones. The stable isotope record shows only minor excursions of the δ 13 C, with values below 0.5‰, and typically varying from 0.7‰ to 1.2‰ V-PDB; the most negative peak δ 13 C = 0.2‰ V-PDB is recorded in the uppermost Crassicollaria Zone. A slightly negative shift of carbon isotope values exceeds about 0.2‰ at the J/K boundary. A similar trend at the critical J/K boundary interval (base of the Calpionella Zone) is seen in several Tethyan sections. The δ 18 O curve shows larger excursions varying between −1.4 and −4.3‰ V-PDB in the J/K boundary interval. Highlights: A new record of the macrofauna (rhyncholites, belemnites, elasmobranchs) from the Jurassic/Cretaceous boundary interval. The macrofauna occurrence in the calpionellid abyssal succession (below the aragonite CCD). Possible tsunamite-like deposits. Biostratigraphically calibrated δ 13 C and δ 18 O stable isotope data from the J/K transition of the Outer Western Carpathians.